Odpowiedzi

Najlepsza Odpowiedź!
2009-09-09T20:03:41+02:00
A) (1/3-1/2)*(1/3+1/2) : 0,5- (0,5)²=(2/6-3/6)*(2/6+3/6):1/2-1/4=
(-1/6)*(5/6):1/2-1/4=5/36*2-1/4=5/18-1/4=10/36-9/36=1/36

b) (√18-√8+√50-1)√2=(3√2-2√2+5√2-1)√2=(6√2-1)√2=12-√2

c)-3²*2:7²-3²=-9*2:49-9=-18:49-9=-18/49-9= -9 18/49
2009-09-09T20:27:42+02:00
A) (1/3-1/2)*(1/3+1/2) : 0,5- (0,5)²=(2/6-3/6)*(2/6+3/6):1/2-1/4=
(-1/6)*(5/6):1/2-1/4=5/36*2-1/4=5/18-1/4=10/36-9/36=¹/₃₆

b) (√18-√8+√50-1)√2=(3√2-2√2+5√2-1)√2=(6√2-1)√2=12-√2

c)-3²*2:7²-3²=-9*2:49-9=-18:49-9=-18/49-9= -9 ¹⁸/₄₉